Integrating Public Health and Clinical Care to Improve Population Health Outcomes - Suprapto Suprapto (Journal Interdisciplinary Health, 2025)
Health systems worldwide continue to face complex challenges related to rising disease burden, health inequities, and fragmented service delivery. The separation between public health and clinical care often limits the effectiveness of preventive and curative interventions in improving population health outcomes. This study aimed to examine the relationship between the integration of public health and clinical care and population health outcomes. A quantitative observational study with a longitudinal approach was conducted involving 50 healthcare professionals from primary healthcare facilities and public health institutions. Data were collected using structured questionnaires to assess levels of service integration and secondary health system data to measure population health outcomes. Statistical analyses included descriptive statistics and regression analysis to determine associations between integration indicators and health outcomes. The findings showed that higher levels of public health–clinical care integration were significantly associated with improved preventive service coverage (? = 0.42; p < 0.001) and increased early disease detection rates (? = 0.39; p = 0.003). Additionally, greater integration was linked to a reduction in avoidable hospital admissions (? = ?0.36; p = 0.012). These results indicate that coordinated preventive and curative services contribute positively to population health performance. Integrating public health and clinical care is associated with measurable improvements in population health outcomes. Strengthening collaboration, referral coordination, and shared information systems may enhance health system efficiency and equity. Integrated service models should be prioritized as a strategic approach to improving sustainable population health outcomes